Modulation of the angle of rigid ankle-foot orthosis to control knee hyperextension in children with unilateral cerebral palsy - Shafeek, Marian M.; Aly, Sobhy M.; Ahmed, Yomna F.; Ibrahim, Hoda M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The aim of this study was to compare the effects of a modified 5° dorsiflexion ankle-foot orthosis (AFO) to the traditional right angle rigid AFO on controlling knee hyperextension and improving spatiotemporal gait parameters in children with unilateral cerebral palsy (CP). We used a pretest-posttest experimental design in which forty children (2-6 years) of both genders with unilateral CP were randomly assigned into two equal groups (A and B). Group A used a traditional right angle rigid AFO and received a selective exercise program to enhance walking pattern while group B used a modified 5° dorsiflexion rigid AFO and received the same exercise program as group A. Assessments for the knee angle during mid-stance and spatiotemporal gait parameters were done pre and post-intervention programs for both groups. All statistical analyses were conducted using the Statistical Package for Social Studies (SPSS) version 25 for windows (IBM SPSS, Chicago, IL, USA). There was a significant decrease in the knee angle in mid-stance post-treatment in groups A and B compared to pre-treatment (p < 0.001) but a significant increase in spatiotemporal gait parameters post-treatment in groups A and B compared to pre-treatment (p < 0.001). There was a significant decrease in the knee angle in mid-stance of group B compared to group A in post-treatment (p > 0.001). However, there was no significant difference in spatiotemporal gait parameters between groups post treatment (p > 0.05). In conclusion, using a rigid AFO improves the spatiotemporal gait parameters and decreases knee hyperextension for children with unilateral CP. Furthermore, a modified 5° dorsiflexion rigid AFO is recommended for better control of knee hyperextension than a traditional right angle rigid AFO for such cases.